Impact of treatment interruption on the efficacy and safety of vunakizumab in patients with moderate-to-severe plaque psoriasis: a post-hoc analysis of a phase 3 trial - Li, Qunyan; Yao, Weifeng; Lei, Dongyun; Xu, Yan; Zhang, Litao; Zhao, Zuotao; He, Junchen; Guo, Tao; Li, Junying (Frontiers in Immunology, 2026)
ObjectiveVunakizumab, a novel IL-17A inhibitor, has demonstrated satisfactory efficacy and safety for the treatment of moderate-to-severe plaque psoriasis. This analysis aimed to assess the impact of treatment interruption on the efficacy and safety of vunakizumab in the treatment of this disease.MethodsThis post-hoc analysis used data from a phase 3 trial of vunakizumab (NCT04839016) that enrolled patients with moderate-to-severe plaque psoriasis. A total of 460 patients received vunakizumab treatment and were included in this analysis.ResultsOver the 52-week treatment, 223 patients had one or more treatment interruption, and 237 patients had no treatment interruption. At week 52, patients with treatment interruption had lower achievement rates for Psoriasis Area and Severity Index (PASI) 75 (77.1% vs. 97.9%), PASI 90 (67.3% vs. 94.1%), PASI 100 (49.8% vs. 75.9%), and static Physician’s Global Assessment of 0/1 (62.8% vs. 93.7%) than those without interruption (all P<0.001). Additionally, at week 52, patients with treatment interruption had lower improvements in patient-reported outcomes (PROs), including Dermatology Life Quality Index score, Itch Numerical Rating Scale score, EuroQol-5D and visual analogue scale score, and Short Form-36 Mental Component Score than those without interruption (all P<0.05). Further subgroup analysis indicated that the increased frequency of treatment interruption correlated with poorer PASI responses and PROs (all P<0.05). The incidence of overall adverse events was similar between the two groups.ConclusionInterrupted vunakizumab treatment reduced the clinical response and quality of life in patients with moderate-to-severe plaque psoriasis.